Property registration in Albania : an information management issue - Sherko, Romeo; Sula, Naim; University of Wisconsin--Madison. Land Tenure Center.; Albania. Immovable Property Registration and Market Action Plan (Project). Project Management Unit. (Land Tenure Center, University of Wisconsin-Madison, 1997)
This paper presents the plans being made in Albania to establish an immovable property registration system in the most efficient way. It considers not only technically modern equipment and computer-related problems but also social and economic feasibility. In Albania, the immovable property registration system is necessary in order to face successfully the new conditions of the free market-oriented economy. For about 50 years, property ownership in Albania was restricted to the State. The 1991 land reform in Albania advanced quickly, and at present over 90 percent of agricultural land is distributed to farmers, though in highly fragmented holdings (totaling an average area average of 2 hectares), creating about 1.8 million new parcels registered in the cadastral district offices. In urban areas, housing privatization was also completed quickly, creating about 300,000 new properties in cities, which are being registered in the Hipoteka (deed registry) district offices. Although market transactions in agriculture land are not yet allowed (though enabling legislation is expected to be passed soon), many land transactions have taken place. The housing market is already very active. Conflicts exist, especially in urban areas, between ex-owners of the land and buildings, and the state or present occupants. Therefore, it is highly desirable to establish a property registration system in Albania quickly and yet with careful planning. This paper presents the registration information system model.
iv, 8 p.
Keywords: Land titles Albania; Land titles Registration and transfer Albania; Land use Information services Albania